ScrumOntoBDD: uma abordagem baseada em Scrum, ontologia e BDD para o desenvolvimento ágil de software - Souza, Pedro Lopes de (2018)
Most Brazilian universities employ traditional teaching-learning methodologies based on lectures classes. The Federal University of São Carlos (UFSCar) is not an exception, but some of its programmes employ active learning methodologies, such as Problem Based Learning (PBL). The Ubiquitous Computing Group (UCG) of UFSCar, which was established in 2002, has been developing projects focused mainly on the Education and Health areas, and recently coordinated the development of the project Educational and Academic Management System for Courses Based on Active Learning Methodologies (EAMS-CBALM). The Scrum agile method was employed in the EAMS-CBALM development, with periodic meetings involving developers and Product Owners (POs) for planning and analyzing the different EAMS-CBALM development phases. It was quite often necessary to redefine some system behaviour scenarios, due to ambiguities present in requirement specifications, or due to misinterpretations of stories reported by POs. The definition of test suites was also cumbersome, resulting in test suites that were incomplete or did not at all comply with the system requirements. Based on this experience and to deal with these problems, this work proposes the ScrumOntoBDD approach, which combines Scrum, Ontology and Behaviour-Driven Development (BDD), for agile software development. This approach explores the concepts and techniques of SCRUM and BDD, focusing on the planning and analysis phases of software life cycle, since the BDD tools provide little support to these phases, and most of the problems found in the EAMS-CBALM development were in those phases. ScrumOntoBDD employs ontologies in order to eliminate ambiguities intrinsic to the use of a natural language as a BDD ubiquitous language.